Pengaruh Kualitas Pelayanan Terhadap Kepuasan nasabah PT Pegadaian (Persero) UPC Titi Kuning Medan - Aqila Tamima; Wahyu Syarvina (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to determine the effect of pawn service quality on customer satisfaction at PT. Pegadaian (Persero) UPC Titi Kuning Medan. The research object is limited to the service quality variable as the independent variable and customer satisfaction as the dependent variable. The sample taken was 86 respondents. The research method used by the author is the descriptive method, which is a method for researching the status of a group of people, an object, a set of conditions or a set of thoughts. The service quality variable is able to explain changes in customer satisfaction at PT. Pegadaian (Persero) UPC Titi Kuning Medan was 29.2% and the remaining 70.8% was explained by other factors not included in this research model. Based on the results of hypothesis testing with the t test, it was obtained that the t count variable for customer satisfaction with service quality was (5.879 > 1.988) that Ha was accepted and Ho was rejected. So it can be concluded that service quality has a significant effect on customer satisfaction. It is recommended to PT. Pegadaian (Persero) UPC Titi Kuning Medan to maintain and improve the quality of service by influencing, encouraging and mobilizing customers to come back to Pegadaian.